(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
Conscientious objection is an “exemption right”, providing exceptions to legal rules; as such, it must be clearly defined. This paper deals with conscientious objection to abortion and to ART, with regard to some recent cases occurred in the Italian legal system. These cases are considered as examples of the difficult relationship between legal rules and pluralism.